Indonesia’s Food Security and Food Sovereignty Under Agricultural Trade Liberalization - Indriastuti, Suyani; Hara, Abubakar Eby; Patriadi, Himawan Bayu; Trihartono, Agus; Sunarko, Bagus Sigit (Global Strategis, 2024)
Agricultural trade liberalisation affects food security and food sovereignty in Indonesia. This article aims to analyse the extent to which agricultural trade liberalisation impacts food security and food sovereignty, as well as examine the dilemmas faced by the Indonesian government related to agricultural liberalisation, food security, and food sovereignty. This research applies qualitative process-tracing case studies using primary data from interviews and secondary data by analysing documents, news, or statistical data provided by institutions such as Indonesian National Statistics, the Food and Agricultural Organization (FAO), and other institutions. This research found that agriculture is a comparative advantage of Indonesia. It supports the achievement of a surplus balance of trade in the global agricultural markets. However, it is challenging and dilemmatic in the context of food commodities. In the short term, agricultural liberalisation might support the achievement of food security as it provides availability of food and food access both physically and economically. However, at the same time, agricultural liberalisation also threatens food sovereignty as it raises dependence on food imports. In the long run, dependency on food imports could endanger food security if there is a change in the political economy of the global market system.Keywords: Liberalisation of Agriculture, Food Security, Food Sovereignty Liberalisasi pertanian mempengaruhi ketahanan pangan dan kedaulatan pangan di Indonesia. Artikel ini bertujuan untuk menganalisis sejauh mana dampak liberalisasi pertanian terhadap ketahanan pangan dan kedaulatan pangan serta dilema yang dihadapi pemerintah Indonesia terkait liberalisasi pertanian, ketahanan pangan, dan kedaulatan pangan. Penelitian ini menerapkan metode kualitatif process-tracing analisis dengan menggunakan data primer yang diperoleh melalui interview dan data sekunder dikumpulkan dengan metode “desk research” termasuk menganalisis dokumen, berita, atau data statistik yang disediakan oleh lembaga-lembaga seperti Statistik Nasional Indonesia, Organisasi Pangan dan Pertanian (FAO), dan lembaga lainnya. Penelitian ini menemukan bahwa pertanian merupakan keunggulan komparatif bagi Indonesia yang mendukung pencapaian surplus neraca perdagangan komoditas pertanian di pasar global. Namun, dalam konteks komoditas pangan, permasalahan bersifat kompleks dan dilematis. Dalam jangka pendek, liberalisasi pertanian dapat mendukung pencapaian ketahanan pangan karena menyediakan ketersediaan pangan yang dapat diakses oleh masyarakat dengan harga yang terjangkau. Namun, pada saat yang sama, liberalisasi pertanian juga mengancam kedaulatan pangan karena meningkatkan ketergantungan pada impor pangan. Dalam jangka panjang, ketergantungan impor pangan dapat membahayakan ketahanan pangan jika terjadi perubahan struktur ekonomi politik pada sistem pasar global.Kata-kata Kunci: Liberalisasi Pertanian, Ketahanan Pangan, Kedaulatan Pangan